Research and application of ‘three zones’ range within overlying strata in goaf of steep coal seam - Yang, Shouguo; Xu, Ning; Liu, Haoxin; Zhang, Xiaofei; Mei, Shuxin (Frontiers in Energy Research, 2024)
The determination of the 'three zones' range within the overlying strata in goaf of paramount importance for effective gas extraction in the goaf and the prevention and control of gas levels exceeding limits in both the working face and the upper corner. Due to the influence of their dip angles, the existing formula used to calculate the breaking boundary angle of the overlying strata in the goaf of horizontal coal seams is no longer suitable for steep coal seams. In response to this issue, the movement law of the overlying strata during the mining of steep coal seams was analyzed and a formula for calculating the breaking boundary angle of the overlying strata in the goaf of steep coal seams was derived. The theoretical calculation formula was applied to the 3103 fully mechanized mining face of a certain mine in southwest China, and compared and analyzed the results with numerical simulation and on-site measurement using microseismic monitoring technology. The research findings demonstrate that the formula effectively quantifies the 'three zones' range within the overlying strata in the goaf of steep coal seams. The 'three zones' range in steep coal seams is primarily influenced by factors such as the length of the filling area in the lower part of the goaf, changes in roof lithology, coal seam dip angle, length of the working face, and overburden load. The longer the length of the filling area, the larger the upper breaking boundary angle and the smaller the lower breaking boundary angle of the fracture zone. Based on the research results of three methods, the height of the caving zone in the 3103 fully mechanized mining face is from 6.93m to 7.7m, the height of the fracture zone is from 28.91m to 34.2m, the lower breaking boundary angle of the fracture zone is from 40° to 44.5°, and the upper breaking boundary angle of the fracture zone is from 57.7° to 62°. The research results offer robust technical support and theoretical guidance for the determination of the 'three zones' range within the overlying strata during the future mining of steep coal seams.